Periodontitis and Serum Interleukin-6 Levels in the Elderly - Miyazaki, Hideo; Murata, Takatoshi; Hanada, Nobuhiro; Senpuku, Hidenobu (Japanese Journal of Infectious Diseases, 2001)
The elderly lose teeth as a result of dental caries and periodontitis caused by pathogenic oral bacteria. Periodontitis produces inflammatory cytokines due to the presence of lipopolysaccharides from oral gram-negative bacteria. Although the number of circulating inflammatory cytokines is related to the severity of the periodontitis, it is unclear whether the concentrations also correlate with periodontitis in the elderly. We investigated the relationship between periodontitis status and the concentrations of serum interleukin-6 (IL-6) in the serum from 276 subjects of 70- and 80-year-olds. Of the 276 subjects, 227 (82%) were dentate, 149 (54%) were found to be positive for serum IL-6, and 29 (13%) of the dentate subjects had severe periodontitis. However, there were no significant differences between the severity of periodontitis or the number of teeth and the mean serum IL-6 concentrations. These results provided no evidence to support an association between circulating IL-6 and periodontitis in the elderly.